The Importance of Correct Diagnosis of Crocodile Tears Syndrome - Oliveira, Danila de [UNESP]; Silva Gomes-Ferreira, Pedro Henrique [UNESP]; Carrasco, Leandro Carlos; Duailibe de Deus, Ciro Borges [UNESP]; Garcia-Junior, Idelmo Rangel [UNESP]; Faverani, Leonardo Perez [UNESP] (Lippincott Williams & Wilkins, 2016)
The excessive unilateral tearing as a result of gustatory stimuli is a characteristic of crocodile tears syndromes. The aim of this study is to report 2 cases of Frey and crocodile tears syndromes, considering diagnosis, monitoring, and selection of appropriate treatment. A 74-year-old female patient presented with a history of Bell palsy, tearing on left eye at the moment of chewing, and absence of pain. The patient opted only for periodic case monitoring because the symptoms presented by the syndrome did not bother her, which made any invasive procedure unnecessary, and with the closed diagnosis she may be reassured and really know what was happening to her. So scientific divulgations about this syndrome should be made in order to increase the knowledge of dentists and oral and maxillofacial surgeons, because it is a rare syndrome and easily diagnosed. Due to the low knowledge in Brazil, the patient of this report had to wait about 9 years to get a diagnosis.
Keywords: Bell palsy; lacrimal apparatus; treatment outcome